Calculation Analysis of Wire Feeder Power Delivery Efficiency on LineX – Y, Middle Java - Supriyadi, Edy; Iriandi Ilyas; Ariman; Raihan Shodiq (Green Publisher, 2023)
The electric train (KRL) is a form of application of scientific and technological developments in the field of transportation so that KRL can replace modes of transportation that use coal or use diesel. Currently electric trains in Indonesia are one of the modes of transportation that are most widely used every day for activities ranging from transportation for schools and colleges to transportation used to go to work and other important activities. Every year electric train passengers in Indonesia are increasing, starting from 100 thousand passengers per day until it is predicted to be 1 million passengers per day. The capacity of the Purwosari Traction Substation (GT) can be categorized as sufficient, with the difference between the specifications of the power capacity and the calculated capacity of only 57.9%. On the Purwosari – Solo Balapan route, the cable type resistance was 0.000167 ?/m, from this type of resistance to the resistance calculated from usage, a difference of around 20.9%. As for the Feeder Wire type resistance, the cable specification limit with the calculation is still below the maximum limit so it is still feasible to use. Because the specification limit and the calculation results are around 99.654% of the limit at 20°C.